Computational analysis of viscoelastic fluid dynamics with applications to heat exchangers - Mavi, Anele (Department of Mathematics and Applied Mathematics, 2019)
In this study, the computational analysis of a pressure driven viscoelastic fluid in a double pipe heat exchanger set-up is investigated. Non-Newtonian viscoelastic fluids in heat exchanger arrangements are encountered in various industrial applications such as power generation, refrigeration and in the food processing industry where the need for cooling and heating of liquids is required. The model problem is governed by complex, non-linear and coupled partial differential equations. These are solved using the semi-implicit finite difference method integrated with the Crank-Nicolson scheme. The pressure-velocity coupling in the momentum equations is resolved by employing the Semi-Implicit Method for Pressure Linked Equations (SIMPLE). To cope with numerical diffusion and numerical stability issues the treatment of convective terms using the upwind schemes is explored. In this work, the behaviour of viscoelastic fluids is rigorously examined by analysing the convective heat transfer from the viscoelastic core fluid of the double pipe heat exchanger to the Newtonian or viscoelastic shell fluid in the outer annulus. In addition, the effects of pressure, momentum, extra stresses, temperature, viscosity and relaxation time on the fluid temperature are investigated; both in the counter flow and parallel flow configurations. Graphical computational results are presented and discussed quantitatively and qualitatively with respect to several parameters involved in the problem.